Model Keterpaduan Jadual Tanam Dan Tebang Tebu: Pendekatan Kompromi - Wayan R. Susila; M. Parulian Hutagaol (School of Business, Bogor Agricultural University (SB-IPB), 2005)
One of the main problems causing a setback of Indonesian sugar industry is inefficiency in farm and plont levels because of lack of integratedproduction system. In response to this problem, this study is aimed at building a model of integratedproduction systems between form and sugar plont activities through on integrotedplonting and horvesfingschedule. The opproach used is a compromise opproach using a multiparty multi objective (MPMO) models. The results of this study show that productivity in farm and sugar plant can be improved by developing an integrated production system through an integratedplanting and harvesting schedule. With supervisions and model modication, the MPMO model can be applied, especially for sugar plantation in Java. Keywords : Sugar Industy, MPMO Model, Tebu, Model Kompromi